Design of an open source framework for oil spill decision support system - Mokhtari,Sahar; Kadlec,Jiri (PeerJ Preprints, 2016)
Oil spill in marine ecosystems have serious short term and long term effects on aquatics lifecycle and on social and economic activities. A Decision Support System (DSS) can assist environmental managers to visualize the distribution of oil pollution, identify sensitive areas that are likely to be exposed to oil pollutions, and assess vulnerable resources. This paper describes the design of an open source software framework and a prototype desktop software application of a DSS for oil spill management. This system can be connected to an open source oil spill simulation model. We also present a user interface for selecting the properties, time and location of a potential oil spill and for visualizing the oil spill affected area and its impact on coastal zone.
Keywords: decision support system; oil spill; open source; coastal zone; software design; geographic information system